Faktor- faktor yang Mempengaruhi Profitabilitas pada Perusahaan Property dan Real Estate di Bursa Efek Indonesia - Suliyanti, Neni; Damayanti, Damayanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to analyze the effect of capital structure, sales growth, company size, and working capital on profitability in Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX). This type of research is quantitative research. The population used in the study in Property and Real Estate companies listed on the Indonesia Stock Exchange as many as 30 companies. The sample in this study was obtained by purposive sampling method, namely the selection of samples with predetermined criteria. The number of samples obtained were 25 Property and Real Estate companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The data collection technique used in this study is secondary data obtained from the financial statements of Property and Real Estate companies listed on the Indonesia Stock Exchange. Multiple linear regression analysis method. The results of this study indicate that capital structure has a significant positive effect on profitability, sales growth has an insignificant negative effect on profitability, company size has a positive and insignificant effect on profitability and working capital has an insignificant positive effect on profitability in Property and Real Estate companies in the 2017-2020 period.Keywords: capital structure, sales growth, company size, working capital, profitability.